Adding time dimension as a shaping parameter of architectural form (chrono form): fusing time and space in chronoform wayfinding. (18th December 2017) - El Sayary, Samer
Abstract: The concept of fusion of time and space in this paper known as chronoform is a concept that re-introduce the spacetime fusion as a developed descendant of chronophotography founded more than 100 year ago using computer. Research findings in spacetime in the hierarchy of wayfinding process (node, path & Survey) by the chronoform could be identified into the following three points: (1) The events in frames of motion vs. landmarks perceived by the user gives clues of spacetime. (2) The motion trajectories timeline creating the path knowledge. (3) The whole motion narrative vs. the survey knowledge. Einstein proved that time is relative, not absolute as Newton claimed. This relativity is achieved during the user movement inside the architectural form. Where he can in a few minutes' experience what others can't see while they are standing still outside the form. The faster they move under the influence of the accelerating rhythm achieved by the chronoform module, the slower their time will pass relative to someone planted firmly outside the architectural form. It is suggested in this study to create an array of void openings using chronoform technique synchronized on time frames across a sun path giving position and time clues. Abstract : Chronoform Synchronizing user movement with the timed event